2023
DOI: 10.2147/dmso.s391369
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium is Inversely Associated with Body Composition and Metabolic Syndrome

Abstract: Purpose Magnesium is vital to maintain normal physiological functions. We aimed to identify the association between serum magnesium and different measures of body adiposity among Qatari adults. We hypothesized that the association was mediated by depression and sleep duration. Patients and Methods The study included 1000 adults aged 20 years and above who attended the Qatar Biobank Study (QBB) between 2012 and 2019. Body adiposity was assessed using dual-energy X-ray ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Indeed, the National Health and Nutrition Examination Survey (NHANES) 3 study demonstrates that Mg2+ deficiency is more common in obese people [ 58 ]. Al Shammaa et al , reported that obese people have decreased levels of magnesium in their bloodstream [ 59 ]. In this study, serum levels of Mg were significantly lower in obese males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the National Health and Nutrition Examination Survey (NHANES) 3 study demonstrates that Mg2+ deficiency is more common in obese people [ 58 ]. Al Shammaa et al , reported that obese people have decreased levels of magnesium in their bloodstream [ 59 ]. In this study, serum levels of Mg were significantly lower in obese males and females.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, a recent cross-sectional study including 1000 adults, found that a 1-SD increment of serum magnesium was associated with reduced odds of MetS (OR: 0.70 [95% CI 0.57-0.85]). 28 Additionally, a meta-analysis including 3487 individuals found that serum magnesium was approximately 0.19 mg/dL lower in participants with MetS compared to those without MetS, although significant heterogeneity between studies was observed. 10 Notably, there is currently no evidence for the relationship between serum magnesium and incident MetS.…”
Section: Discussionmentioning
confidence: 99%
“…However, this question has been used in previous reports from QBB and similar questions have been used to assess similar outcomes to this study. [34][35][36][37][38][39][40][41] It is important to note that this method of assessment may be subject to recall bias and misclassification of cases and controls. However, it can be assumed that this misclassification is non-differential so would not bias our results but would instead weaken the associations.…”
Section: Discussionmentioning
confidence: 99%